Choker [large type] - Ramsay, Frederick (Ramsay, Frederick. Ike Schwartz mystery., 2009)
Nick Reynolds, his pilots rating barely a month old, drops off the radar at night over the Chesapeake Bay. Investigating agencies call it another tragic pilot error accident. No trace of the plane is found in the Bays murky waters. Ike Schwartz, erstwhile sheriff of Picketsville, on vacation, is approached by Charlie Garland, an old CIA friend, to look into the disappearance. Ikes wide-eyed entry into a simple missing persons case catapults him into an international thriller with intimations of terrorism that might threaten the nation and its leaders.